Paleoenvironment studies of the Pisco formation: Ocucaje locality - Báez Gómez, Diego A. (2006)
The Cerro La Bruja outarop included into Pisco Formation related to fosiliferous content (mollusca and vertebrades) get a exactly datation of series, developed by marine sediments interbeded volcanics of volcanic activities from Cordillera occidental and diatomites, related to volcanics activities. In this Formation were found since thousand mile years a huge faune from marine vertebrates. This fauna is well know and it includes fish (selaceous and teleosteous), reptiles (turtles and cocodriles), binds and marine mamiferos (spheniscidae, phocidae). The funistic association shows sedimentary enviromment represent to this litoestratigrafic unit, go from shoreface to onshore, to abundance and good preservation of fosils shows a fast sandy. The tectonic activity in the area is strong and its shows in the variation from sea level (transgressive – regressive) log in the outcrop up shong marks to seven levels of backward from sea level, showing a relationships to sedimentary process.